SENSING MECHANISM AND APPLICATION OF MECHANICAL STRAIN SENSOR: A MINI-REVIEW - Ha, Heebo; Qaiser, Nadeem; Yun, Tae Gwang; Cheong, Jun Young; Lim, Sooman; Hwang, Byungil (Facta Universitatis, Series: Mechanical Engineering, 2023)
This study reviews the potential of flexible strain sensors based on nanomaterials such as carbon nanotubes (CNTs), graphene, and metal nanowires (NWs). These nanomaterials have excellent flexibility, conductivity, and mechanical properties, which enable them to be integrated into clothing or attached to the skin for the real-time monitoring of various activities. However, the main challenge is balancing high stretchability and sensitivity. This paper explains the basic concept of strain sensors that can convert mechanical deformation into electrical signals. Moreover, this paper focuses on simple, flexible, and stretchable resistive and capacitive sensors. It also discusses the important factors in choosing materials and fabrication methods, emphasizing the crucial role of suitable polymers in high-performance strain sensing. This study reviews the fabrication processes, mechanisms, performance, and applications of stretchable strain sensors in detail. It analyzes key aspects, such as sensitivity, stretchability, linearity, response time, and durability. This review provides useful insights into the current status and prospects of stretchable strain sensors in wearable technology and human–machine interfaces.
Keywords: Basic concepts; Electrical signal; Flexible; Mechanical deformation; Mechanical strain; Metal nanowire; Real time monitoring; Sensing applications; Sensing mechanism; Strain sensors; Deformation; Flexible; Mechanical Property; Nanomaterials; Strain Sensor